Evaluating Community Outreach Efforts: A Framework and Approach Based on a National Mental Health Demonstration Project - Brenda Morissette Joly; Martha Elbaum Williamson; Kimberly Pukstas Bernard; Prashant Mittal; Jennifer Pratt (The Evaluation Center at Western Michigan University, 2011)
Background:  Community health efforts often include outreach activities designed to increase awareness and ensure uptake of services or programs.  Yet, few comprehensive outreach evaluations exist, particularly those designed to improve access to and use of mental health services.    Purpose: This article summarizes the use of two established evaluation frameworks and details an approach to assessing outreach that may have broad appeal to administrators, social workers, health educators, community organizers, and others interested in exploring the results of their efforts.    Setting: Multi-site national study conducted in five states   Intervention: Community outreach   Research Design: Two existing published frameworks are applied to assess community outreach.  The evaluation design included three components: 1) process, 2) outcomes and 3) context.   Data Collection and Analysis: Qualitative data were based on focus groups and key informant interviews.  Quantitative data were gathered through evaluation surveys, tracking forms and other outreach protocols.  The findings focus on lessons learned that may have applicability to others interested in evaluating community outreach efforts in areas beyond mental health.